Precarious professionality: graduate outcomes and experiences from an Initial Teacher (Further) Education programme in Ireland. Issue 1 (2nd January 2020) - O'Neill, Jerry; Fitzsimons, Camilla
ABSTRACT: This article presents and discusses the findings of a small-scale research project into the occupational outcomes of graduates of an Initial Teacher (Further) Education (ITE) programme at Maynooth University in Ireland. The findings from this mixed-method research indicate that many graduates experience high levels of occupational precarity and a sense of professional inequity when compared with their compulsory education teacher-peers as they attempt to make the transition into the heterogeneous field of adult and Further Education in Ireland.